The Social Competencies of Pesantren Teachers in Shaping Students' Character in the Digital Era - Asep Supriatna; Abdussalam DZ; Abdul Karim; Jalaludin Jalaludin; Maftuhah Dewi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to analyze the development of social competencies among pesantren teachers in shaping students' character in the digital era. This qualitative research was conducted at Al-Khoir Islamic Boarding School in Karawang, involving 10 teachers and 15 students. Data were collected through semi-structured interviews, observations, and document analysis, and analyzed using a thematic analysis framework based on the work of Miles and Huberman. The findings show that teachers at Al-Khoir demonstrate social competence through role modeling, empathetic communication, and the instilling of moral values in daily routines. However, there are challenges in digital literacy, as teachers struggle to integrate digital tools into their teaching due to limited resources and inadequate training. This gap in digital competence is influenced by the pesantren’s traditional values and leadership style, which prioritize religious education over technological integration. These findings contribute to the literature on teacher social competence and character education by highlighting the importance of enhancing digital competencies in teachers. The study offers practical recommendations for integrating digital literacy training into professional development programs at pesantren, enabling teachers to navigate the digital era more effectively and enhance their character-building efforts. Furthermore, this research offers valuable insights for both theory and practice, suggesting that strengthening digital literacy in teacher training programs is crucial for preparing educators to effectively navigate the challenges of the digital age while promoting character development in students.